Old and New anticoagulants: The beginning of a new era? - Fidel Cáceres Loriga; Aida Crespo Guerra (ECIMED, 2011)
Use of coumarin and heparin for more than sixty years, has been an effective and powerfulmedical tool for treatment and prevention of thromboembolic diseases, tarnished nevertheless,by their little security and laboratory controls which are frequently needed. Such reasonsmake for an effective challenge and an active field, searching the ideal anticoagulant inscientific investigation, drugs to inhibit specific clot factors, able to exclude the weak pointsof the available ones is its goal. In this article, we consider physiopathology for thrombi formationand we review too the history, pharmacokinetics and pharmacodynamic properties ofold anticoagulants drugs, their limitations, just when new anticoagulants drugs haveemerged as inhibitors of thrombin or Xa factor, whose effectiveness and security are beingcontrasted with the traditional ones in wide programs of current execution with atrial fibrillationand coronary syndromes included, and they could potentially substitute the old ones ina near future.